El cáncer de colon y recto en cuidados paliativos: una mirada desde los significados del paciente (2015)
This research aimed to understand the meaning and personal coping process of three end-stage colorectal cancer patients receiving palliative care. The metodology was qualitative, with a phenomenological approach. By way of in-depth interviews, we explored beliefs and obtained information from the patients about the origin of the disease, the expression of emotions and resources and obstacles for coping. Results allowed us to understand that the patient's meaning constructed around the diagnosis relates to previous experiences, knowledge of the disease, and the presence or absence of symptoms. Importantly, patients did not perceive the disease as a threat, they felt calm about the diagnosis and were not conscious of the proximity of death. Emotional expressions ranged from sadness, surprise, and distress at diagnosis, to acceptance, trust in God, trust in the medical treatments as a way of healing. Adherence to medical advice and trust in God became main strategies for coping with the disease.